Metformin‐mediated mitochondrial protection post‐cardiac arrest improves EEG activity and confers neuroprotection and survival benefit. Issue 5 (8th April 2022) - Shoaib, Muhammad; Choudhary, Rishabh C.; Chillale, Rupesh K.; Kim, Nancy; Miyara, Santiago J.; Haque, Shabirul; Yin, Tai; Frankfurt, Maya; Molmenti, Ernesto P.; Zanos, Stavros; Kim, Junhwan; Becker, Lance B.
Abstract: Cardiac arrest (CA) produces global ischemia/reperfusion injury resulting in substantial multiorgan damage. There are limited efficacious therapies to save lives despite CA being such a lethal disease process. The small population of surviving patients suffer extensive brain damage that results in substantial morbidity. Mitochondrial dysfunction in most organs after CA has been implicated as a major source of injury. Metformin, a first‐line treatment for diabetes, has shown promising results in the treatment for other diseases and is known to interact with the mitochondria. For the treatment of CA, prior studies have utilized metformin in a preconditioning manner such that animals are given metformin well before undergoing CA. As the timing of CA is quite difficult to predict, the present study, in a clinically relevant manner, sought to evaluate the therapeutic benefits of metformin administration immediately after resuscitation using a 10 min asphxyial‐CA rat model. This is the first study to show that metformin treatment post‐CA (a) improves 72 h survival and neurologic function, (b) protects mitochondrial function with a reduction in apoptotic brain injury without activating AMPK, and (c) potentiates earlier normalization of brain electrophysiologic activity. Overall, as an effective and safe drug, metformin has the potential to be an easily translatable intervention for improving survival and preventing brain damage after CA.